A deep siamese neural network improves metagenome-assembled genomes in microbiome datasets across different environments - Shaojun Pan; Chengkai Zhu; Xing-Ming Zhao; Luis Pedro Coelho (Nature Communications, 2022)
Here, the authors present SemiBin, a siamese deep neural network framework that incorporates information from reference genomes, able to extract better metagenome-assembled genomes (MAGs) in several host-associated and environmental habitats.